(untitled) (CAHIERS MAGELLANES-NS, 2024)
background: In our current era, marked by the continuous evolution of technology, the emergence of innovative advancements is a daily occurrence. The emergence of 3D printing stands out as a highly anticipated innovation. Given the significance of 3D printing and its substantial potential within the prosthodontics field, this research aims to determine the level of knowledge and attitude toward 3D printing applications among the dentist community in Saudi Arabia. Objective: To assess the knowledge, awareness, and attitude toward 3D printing and its utilization in the field of prosthodontics among dentists, dental students, and interns. Methodology: In a span of eight months, beginning in August 2023 and ending in May 2024, a thoroughly structured cross-sectional study will be carried out in various regions, cities, and communities across the Kingdom of Saudi Arabia. The participants involved in this study will primarily consist of dental students, interns, and licensed dentists. Results: the total sample size were 860 participants with 88.5% were males and 11.5% were females. As regard knowledge and awareness score about application of 3D printing in prosthodontics among dentists and dental students, there were 63.4% of participants exhibited a high level of knowledge and awareness, 9.9% demonstrated a moderate level, and 26.7% showed a low level. As regard attitude score towards the application of 3D printing in prosthodontics among dentists and dental students, there were 77.7% of the total sample, exhibited a positive attitude towards the application of 3D printing in prosthodontics. Conversely, a smaller proportion of respondents, accounting for 8.1%, expressed a neutral stance, while 14.2% displayed a negative attitude. In term of knowledge and awareness, relation to sociodemographic characteristics showed statistically significant relation to gender (p value=0.0001), age (p value=0.0001), address (p value=0.0001) and occupation (p value=0.0001). However, there was a statistically significant relation to gender (p value=0.0001), age (p value=0.0001), address (p value=0.0001) and occupation (p value=0.002) regarding participant’s attitude. Conclusion: the study highlighted the varying levels of knowledge, awareness, and attitude towards the application of 3D printing in prosthodontics among dentists and dental students in Saudi Arabia. While a significant portion of participants demonstrated a high level of knowledge and a positive attitude towards 3D printing, there were still gaps in awareness and understanding of the technology. The findings suggest a promising trend towards the integration of 3D printing in dental practice, with potential benefits including improved accuracy, efficiency, and personalized care for patients. Continued education and training on 3D printing technologies are essential to further enhance its utilization and maximize its potential in the field of dentistry.